The Bahá’í Faith and Covenantal Pluralism: Promoting Oneness, Respecting Difference - Palmer, David A. (The review of faith & international affairs, 2021)
The core teachings of the Bahá’í Faith are often summarized as the “Oneness of God, the Oneness of Religion, and the Oneness of Humanity.” Can such principles resonate with a pluralism based on the recognition of difference? Covenantal pluralism outlines a set of principles of co-existence based on deep respect for difference that acknowledges the exclusive truth claims of different actors. In this article, we examine how the teachings and practices of the Bahá’í Faith relate to this framework of covenantal pluralism. The “covenantal” vision of human solidarity resonates strongly with the Bahá’í Faith’s own conception of “Covenant” as the foundation of its community, internal constitutional order, and ultimate aims, as well as with the Bahá’í understanding and practice of consultative deliberation. However, the test of pluralism is how Bahá’ís engage with those who reject their religion’s truth claims and aspirations to oneness. In this regard, the Bahá’í teachings affirm the legitimacy of other religions, as well as the choice not to be religious. Bahá’í social engagement emphasizes collaboration with people of different religious and ideological backgrounds in community building, social action, and public discourse. A foundational principle of such engagement is the freedom not to accept the Bahá’í Faith or its teachings. Overall, the Bahá’í approach to pluralism is rooted in an affirmation of ontological oneness that is the foundation for honoring, respecting, and engaging with the social reality of diversity.